Cross-Sectional Assessment of Atopic Dermatitis Symptom Frequency Itching, Sleep Disturbance, and Skin Barrier Changes (Bangladesh Journal of Medical Science, 2026)
Background Itch and disruption of the skin’s natural barrier function are major contributors to issues in children with atopic dermatitis, including those that impact their ability to sleep, which in turn affects their ability to function or impacts their caregivers’ ability to function. We sought to determine how often these issues occurred in a week, how severe they were, and what factors were associated with itch and sleep issues in a pediatric population. Methods We conducted a cross-sectional study of children